2007
DOI: 10.1038/nm1688
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of acute and chronic allograft rejection with CD4+CD25+Foxp3+ regulatory T lymphocytes

Abstract: A major challenge in transplantation medicine is controlling the very strong immune responses to foreign antigens that are responsible for graft rejection. Although immunosuppressive drugs efficiently inhibit acute graft rejection, a substantial proportion of patients suffer chronic rejection that ultimately leads to functional loss of the graft. Induction of immunological tolerance to transplants would avoid rejection and the need for lifelong treatment with immunosuppressive drugs. Tolerance to self-antigens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
390
2
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 474 publications
(421 citation statements)
references
References 30 publications
20
390
2
9
Order By: Relevance
“…Moreover, the generation of alloreactive Treg cells from non-Treg precursors by stimulation with alloantigens may offer immunological advantages over polyclonal expansion of naturally occurring Treg cells, as indicated by other authors [67,68]. We have shown that the presence of RA, TGF-β1, and IL-2 consistently induces the de novo generation of regulatory RA-iTreg cells.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, the generation of alloreactive Treg cells from non-Treg precursors by stimulation with alloantigens may offer immunological advantages over polyclonal expansion of naturally occurring Treg cells, as indicated by other authors [67,68]. We have shown that the presence of RA, TGF-β1, and IL-2 consistently induces the de novo generation of regulatory RA-iTreg cells.…”
Section: Discussionmentioning
confidence: 51%
“…Foxp3 has important roles not only as a key molecule in the development of regulatory T cells, but also as an inhibitor of T-cell activation and a repressor of transcription factors (31)(32)(33). Regulatory T cells have been widely used in experimental models for treating autoimmune diseases including IBD (13), arthritis (17), diabetes (18,34), and atherosclerosis (35), allergic diseases including asthma (36) and dermatitis (37), and in preventing transplantation rejection (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, indirect presentation of alloantigens by host regulatory APCs probably is the predominant tolerance mechanism. Other models of allogeneic transplantation also indicate that the indirect pathway plays a critical role in donor-specific tolerance (30,31). Recent data in the EAE model suggest that host plasmacytoid dendritic cells are crucial in this tolerogenic cross-presentation and that the tolerogenic interactions probably occur in the spleen (S.D.M., unpublished observations).…”
Section: Discussionmentioning
confidence: 95%